A Retrospective Study on Erythropoiesis Stimulating Agent Dose Reducing Potential of an Anti‐Platelet Activation Membrane Dialyzer in Hemodialysis Patients. Issue 2 (11th October 2018) - Kakuta, Takatoshi; Ishida, Mari; Komaba, Hirotaka; Suzuki, Hajime; Fukagawa, Masafumi
Abstract: Our previous small‐scale trial demonstrated an erythropoiesis stimulating agent (ESA)‐sparing potential of the TORAYLIGHT NV (NV) dialyzer in hemodialysis patients with high interleukin‐6 levels. We now retrospectively explored this ESA‐sparing potential of the NV dialyzer in 122 and 129 prevalent dialysis patients who were on the NV and conventional polysulfone (PS) dialyzers, respectively, for 12 months. ESA resistance index (ERI) increased with the PS dialyzers whereas neither ERI nor ESA dose changed with the NV dialyzer. Analyses of baseline ERI or ESA dose‐based subgroups revealed a decrease in ERI and ESA dose with the NV dialyzer in patients with a baseline ERI ≥12 IU·dL/week·kg·g Hb ( P  < 0.05) and in those with a baseline ESA dose >6000 IU/week ( P  < 0.001), respectively. Neither ERI nor ESA dose improved in the corresponding subgroups on the PS dialyzers. These findings suggest that NV dialyzer can improve ESA responsiveness in hemodialysis patients with advanced ESA resistance.